2016
DOI: 10.5812/jmb.9771
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasites of Domestic Chicken (Gallus gallus domesticus) in Akure, Nigeria

Abstract: A survey of intestinal parasites of chickens was carried out in Akure, Ondo State, Nigeria from January to December, 2015. A total of 327 chickens of different breeds were examined for gastrointestinal infections. Fecal samples obtained from these chickens were prepared for microscopy using flotation technique. The results showed that 67 (20.5%) of the 327 chickens examined were infected with various gastrointestinal parasites. Among the infected chickens, the layers were the most susceptible to gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 6 publications
5
24
4
2
Order By: Relevance
“…A statistically significant difference was observed in the overall prevalence of gastrointestinal helminths among chickens kept under the backyard, semi-intensive, and intensive management systems. This showed that the prevalence of helminth parasites was decreased with increasing quality and modernization of the production system, which is in agreement with the study conducted in Akure, Nigeria [16]. This might be because of the hygienic environment and feeding system of the chicken in the intensive farms, which is not favorable for helminth parasites growth and transmission [7].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A statistically significant difference was observed in the overall prevalence of gastrointestinal helminths among chickens kept under the backyard, semi-intensive, and intensive management systems. This showed that the prevalence of helminth parasites was decreased with increasing quality and modernization of the production system, which is in agreement with the study conducted in Akure, Nigeria [16]. This might be because of the hygienic environment and feeding system of the chicken in the intensive farms, which is not favorable for helminth parasites growth and transmission [7].…”
Section: Discussionsupporting
confidence: 85%
“…It is comparable with the findings reported from Barisal district, Bangladesh (91.88%), Nairobi County, Kenya (90%), and Hawassa, Ethiopia (88.5%) [13–15]. However, it was high when compared with reports from Akure, Nigeria (20.5%) [16]; this lower prevalence recorded may be because of the relatively small number of chickens (sample size) examined during the Nigerian study that involved only 85 chickens.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, an overall prevalence of 62.9% was recorded in this study, suggesting that helminthoses is an important disease among avian species in the state. Within Nigeria, dispersing prevalence of 100.0%, 86.0%, 81.3%, 27.9% and 11.9% has been reported by Uhuo et al (2013), Attah et al (2013), Adang et al (2014), Jegede et al (2015) and Afolabi et al (2016) in Abakaliki, Sokoto, Gombe, Gwagwalada and Akure respectively. In other parts of the world, prevalence rate of 7.3% has been reported in Iran (Badparva et al, 2015), 10.5% in Trinidad (Baboolal et al, 2012), 51.7% in India (Naphade, 2013) and 100.0% in Zambia (Nalubamba et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…In Nigeria, young birds are mainly kept intensively for the fear of predators, as such reducing their chances of picking up helminth eggs and its intermediate hosts. Afolabi et al (2016) reported the lowest prevalence of avian intestinal parasites in domestic birds raised intensively compared to those raised semi-intensively and extensively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation